2019
DOI: 10.1002/jor.24342
|View full text |Cite
|
Sign up to set email alerts
|

Use of Allogeneic Hypoxic Mesenchymal Stem Cells For Treating Disc Degeneration in Rabbits

Abstract: Intervertebral discs (IVDs) are important biomechanical components of the spine. Once degenerated, mesenchymal stem cell (MSC)‐based therapies may aid in the repair of these discs. Although hypoxic preconditioning enhances the chondrogenic potential of MSCs, it is unknown whether bone marrow MSCs expanded under hypoxic conditions (1% O2, here referred to as hypoxic MSCs) are better than bone marrow MSCs expanded under normoxic conditions (air, here referred to as normoxic MSCs) with regards to disc regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…For the disc, two studies investigated the use of hypoxic preculture before cell implantation and demonstrated decreased loss of disc height, improved matrix protein expression, and improved cell survival. 106,107 One study investigated mechanical loading in a hydrogel system with TGFb1 present before cell implantation and demonstrated improved GAG deposition and SOX9 and collagen II expression. 108 In addition, selection of cells highly expressing TGFb1 and TGFb2 receptors before implantation demonstrated improved tissue morphology while increasing anabolic gene expression.…”
Section: Preconditioningmentioning
confidence: 99%
“…For the disc, two studies investigated the use of hypoxic preculture before cell implantation and demonstrated decreased loss of disc height, improved matrix protein expression, and improved cell survival. 106,107 One study investigated mechanical loading in a hydrogel system with TGFb1 present before cell implantation and demonstrated improved GAG deposition and SOX9 and collagen II expression. 108 In addition, selection of cells highly expressing TGFb1 and TGFb2 receptors before implantation demonstrated improved tissue morphology while increasing anabolic gene expression.…”
Section: Preconditioningmentioning
confidence: 99%
“…To retard the process IVD degeneration or maintain the structure as well as the function of degenerative discs, different rabbit models of disc degeneration have been used with applications of autologous, allogeneic or human derived stem cells as well as chondrocytes with or without genetic modification of the cells or in combination with bioscaffolds 6882 (Table 4). Bone marrow-derived MSCs, synovial MSCs, umbilical cord tissue-derived MSCs, adipose-derived stem cells (ADSCs), and embryonic stem cells (ESCs) have been used with or without in vitro differentiation toward a chondrocyte lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow-derived MSCs, synovial MSCs, umbilical cord tissue-derived MSCs, adipose-derived stem cells (ADSCs), and embryonic stem cells (ESCs) have been used with or without in vitro differentiation toward a chondrocyte lineage. 6878 The regenerative effect of bone morphogenic protein 2 (BMP2), which is known to have biological effects on the differentiation of MSCs into chondrocyte-like cells in platelet-rich plasma (PRP) gel culture, was investigated in a rabbit model of disc degeneration. Autologous bone marrow-derived MSCs transduced with AdV vectors encoding for BMP2 (AdV-BMP2) and loaded in PRP gel (MSC-AdV-BMP2-PRP; 1 × 10 6 cells/20 µL) were directly injected into anular-punctured lumbar discs.…”
Section: Introductionmentioning
confidence: 99%
“…Several favorable results have been observed for stem cell therapy of IVDD. Though transplanted mesenchymal stem cells (MSCs) can differentiate into intervertebral disc (IVD) cells and significantly promote extracellular matrix (ECM) synthesis in IVD tissues (Chiang et al, 2019) and improve clinical outcome (Noriega et al, 2017) of IVDD patients as well, there were unexpected findings obtained in some studies. An aggravation of IVDD was reported after the injection of MSCs into NP tissues because of the formation of osteophytes (Vadala et al, 2012).…”
Section: Introductionmentioning
confidence: 99%